2015
DOI: 10.3923/ajava.2015.226.236
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Exogenous Fibrolytic Enzyme Application on Productive Response of Dairy Cows at Different Lactation Stages

Abstract: This study aimed to evaluate effect of using exogenous fibrolytic enzymes on productive performance of dairy cows and milk curve response at different lactation stages. One hundred and sixteen multiparous cows were randomly assigned into two groups; fifty eight cows in each. Each group was contained 12 cows in early lactation 40±6 Days In Milk (DIM), 18 cows in mid lactation (122±4 DIM) and 29 cows in late lactation (216±2 DIM). The animals were fed total mixed ration with or without 15 g fibrolytic enzymes he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 22 publications
(29 reference statements)
6
7
0
Order By: Relevance
“…Yeast culture or fibrolytic enzyme supplementation did not significantly alter feed intake as DMI, TDN, and DCP (Table 5). The results of our study agreed with other studies (Salem et al 2013;Peters et al, 2015;El-Bordeny et al, 2015), They confirmed that adding enzymes had no effects on dairy cows or DM intake at different stages of lactation. Morrison et al (2001) YC culture was fed from 14 days before delivery to 14 days after delivery, and it had no effect on prenatal DMI.…”
Section: Feed Consumptionsupporting
confidence: 93%
See 2 more Smart Citations
“…Yeast culture or fibrolytic enzyme supplementation did not significantly alter feed intake as DMI, TDN, and DCP (Table 5). The results of our study agreed with other studies (Salem et al 2013;Peters et al, 2015;El-Bordeny et al, 2015), They confirmed that adding enzymes had no effects on dairy cows or DM intake at different stages of lactation. Morrison et al (2001) YC culture was fed from 14 days before delivery to 14 days after delivery, and it had no effect on prenatal DMI.…”
Section: Feed Consumptionsupporting
confidence: 93%
“…These findings are in agreement with Bush (1991), who pointed out that the total serum protein concentration reflects the nutritional status of animals and is positively correlated with dietary protein levels. Also, El-Bordeny et al (2015) found that the blood glucose and total protein concentrations of the FENZ group increased compared with the control group. This was due to the improvement of the metabolic process, especially the increase of the apparent nutrient digestibility, the flow of protein and organic matter in the rumen and the microbial protein in the rumen Caused by.…”
Section: Blood Metabolitesmentioning
confidence: 89%
See 1 more Smart Citation
“…The values of plasma GPT (32.13-39.32 U/l) and GOT (47.60-61.02 U/l) were within normal range indicating fibrolytic microbes and enzymes had no damaging effect on liver and/or muscles of crossbred calves. These findings on effect of treatments were in line with Morsy et al (2016) who indicated similar value of serum ALT (30.1-30.4 units/l) and AST (15.1-15.6 units/l) in Egyptian buffaloes fed two commercial enzymes, and similar were the observations in Holstein dairy cows fed 15 g fibrolytic enzyme (El-Bordeny et al, 2015). Hossain et al (2012) showed non-significantly lower serum AST (94.67 ± 4.99 and 88.67 ± 3.87 vs. 96.67 ± 6.39 μ/L) and higher serum ALT (40.00 ± 3.10 and 38.50 ± 3.49 vs. 37.83 ± 2.14 μ/L) in Kankrej calves fed diet supplemented with live yeast (Saccharomyces cerevisiae) at 5 and 10 g/day than the control group.…”
Section: Plasma Transaminases (Gpt Got)supporting
confidence: 87%
“…Contrary to present finding, Morsy et al (2016) indicated that an individual application of two commercial enzymes both at 40 g/day in total mixed ration of lactating buffaloes showed higher (p = 0.091) serum total protein (8.31 and 8.11 vs. 6.99 g/dL) in comparison to control. El-Bordeny et al (2015) found a significant increase (p < 0.05) in total serum proteins (8.83 ± 0.30 and 7.87 ± 0.26 g/dL) of Holstein dairy cows fed 15 g fibrolytic enzyme plus TMR. Similarly, higher (p < 0.05) total protein (6.68 ± 0.18 vs. 5.92 ± 0.25 g/dl) of calves was recorded when fed diet containing 5 and 10 g/day live yeast (Saccharomyces cerevisiae) as compared to control (Hossain et al, 2012).…”
Section: Plasma Total Proteinmentioning
confidence: 87%